Social Media Use and Health: What We Have Known So Far, and What We Need to Investigate in the Future - Shaoyu Ye; Kevin K. W. Ho (Healthcare, 2026)
This review examines the evolving relationship between social media use and health from the perspective of the World Health Organization (WHO), which defines health as a state of complete physical, mental, and social well-being. Drawing on recent empirical findings and systematic reviews, this paper synthesizes current evidence regarding how social media use relates to the three dimensions of health and may facilitate the spread of health misinformation. As social media has become deeply integrated into daily life, understanding these dynamics is increasingly important for developing evidence-based strategies that promote public health in the digital era. Under the theme “What We Have Known so far,” this review highlights the dual nature of social media as a double-edged sword. On one hand, social media facilitates health promotion, knowledge sharing, social support, and the development of social capital and interpersonal relationships, improving the three dimensions of well-being. On the other hand, excessive or problematic use has been associated with adverse mental, physical and social health outcomes, while exposure to online misinformation poses substantial challenges to effective public health communication. This review further emphasizes that social media impacts vary across platforms, user characteristics, patterns of engagement, and combinations of platforms. Under the theme “What We Need to Investigate in the Future,” several research priorities are identified. These include adopting an integrated framework that simultaneously considers physical, mental, and social health; moving beyond cross-sectional designs toward longitudinal and causal approaches and examining platform-specific effects and the influence of individuals’ broader social media portfolios; incorporating objective behavioral measures alongside self-reported data and investigating the emerging role of generative artificial intelligence in health communication and misinformation; and developing evidence-based interventions to improve social media literacy and promote healthier patterns of use. Overall, this review argues that future research should move beyond asking whether social media is beneficial or harmful to health and instead identify when, how, for whom, and under what circumstances it promotes or compromises well-being. Such an integrated perspective will provide a stronger scientific foundation for public health policies and healthier digital societies.